An additive for low-energy consumption electrolytic preparation of iron powder and a preparation method and application thereof
Patent Information
- Application Number
- CN202611170958.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-04
AI Technical Summary
[0004]尽管电解法在铁粉制备中具有诸多优势,但实际工业化应用中仍存在一定的技术瓶颈,主要体现在成粉临界电流密度高,传统电解铁粉工艺通常需要在大于1000 A/m²的电流密度下进行,高电流密度下析氢副反应剧烈,生产过程中能耗激增;而低电流密度下易形成片状沉积物,无法直接获得粉末状产物
1.本发明通过乙烯基叔丁基醚经阳离子聚合、羧甲基化改性成功制备了可电沉积铁粉的添加剂羧甲基聚乙烯醇,该添加剂能够有效降低形成铁粉的临界电流密度,大幅降低电沉积铁粉的能耗。
Smart Images

Figure CN122668301B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrolytic preparation of metal powder technology, specifically relating to an additive for low-energy electrolytic preparation of iron powder, its preparation method and application. Background Technology
[0002] Ultrafine high-purity iron powder has a large specific surface area, high activity, and excellent thermal properties, and is widely used in industrial production and high-tech fields. It is not only a core raw material in traditional fields such as powder metallurgy, machinery manufacturing, and chemical catalysis, but also plays an irreplaceable role in cutting-edge fields such as 3D printing, porous metal ceramics, friction materials, rechargeable batteries, and the preparation of high-end alloys.
[0003] Currently, industrial methods for preparing iron powder include reduction, atomization, carbonylation, and electrolysis. Reduction primarily uses iron oxides as raw materials, requiring a large amount of reducing agent during the reduction process. Atomization demands high raw material purity, and precise control of product particle size is difficult. The carbonylation method uses carbonyl compounds that are highly toxic, flammable, and explosive, necessitating extremely high requirements for the sealing and safety of production equipment. Compared to these three processes, electrolysis offers significant advantages such as strong raw material adaptability, high product purity, easily controllable particle size, mild reaction conditions, and a clean process.
[0004] Despite the numerous advantages of electrolysis in iron powder preparation, certain technical bottlenecks remain in practical industrial applications. The main challenge lies in the high critical current density for powder formation. Traditional electrolytic iron powder production typically requires current densities exceeding 1000 A / m², where the hydrogen evolution side reaction is severe, leading to a surge in energy consumption. Conversely, low current densities easily result in the formation of flaky deposits, making it impossible to directly obtain powdered products. Therefore, developing a high-efficiency electrolytic process for iron powder preparation at low current densities is of significant practical importance and holds broad application prospects for promoting the development of high-end manufacturing and overcoming key material bottlenecks. Summary of the Invention
[0005] To address the technical problems of high critical current density for iron powder formation and severe hydrogen evolution side reactions in the electrolytic method for iron powder preparation, this invention aims to provide an additive for low-energy electrolytic iron powder preparation and its preparation method. This invention achieves low-energy, high-efficiency, high-purity, and continuous stable production of ultrafine, high-purity iron powder by adding an additive (carboxymethyl polyvinyl alcohol) to the electrolyte. The addition of carboxymethyl polyvinyl alcohol significantly reduces the critical current density for iron powder formation, thereby reducing energy consumption. Simultaneously, it forms a stable hydrogen bond network in the electrolyte, reducing the number of free water molecules and inhibiting hydrogen evolution side reactions.
[0006] The technical solution adopted in this invention is as follows: A method for preparing an additive for low-energy electrolytic iron powder production includes the following steps: S1: Using vinyl tert-butyl ether as a monomer and boron trifluoride diethyl ether as an initiator, the reaction is carried out in a mixed solution of polar halocarbon solvent and nonpolar hydrocarbon solvent at -20~-10℃ under inert gas protection for 4-8 hours to generate a prepolymer. An excess of the undesirable solvent of the prepolymer is added dropwise to the reaction system, and after precipitation to form a white flocculent prepolymer solid, the prepolymer solid is added to an acidic solution and heated and stirred under reflux. Then, the mixture is filtered, washed, and dried to obtain polyvinyl alcohol. The acidic solution is a mixture of hydrochloric acid and tetrahydrofuran. The reaction formula is as follows: ; Where n is a positive integer; S2: The polyvinyl alcohol is modified by carboxymethylation to obtain carboxymethyl polyvinyl alcohol, which is the additive.
[0007] Further, the molar ratio of the vinyl tert-butyl ether to the initiator is 100:0.8~1.2, preferably 100:1; in step S1, the inert gas is nitrogen or argon.
[0008] Furthermore, in step S1, the reaction temperature for generating the prepolymer is -20 to -15°C, and the reaction time is 5 to 6 hours.
[0009] Further, in step S1, in the mixed solution of polar halocarbon solvent and nonpolar hydrocarbon solvent, the polar halocarbon solvent is dichloromethane or chloroform, and the nonpolar hydrocarbon solvent is toluene, n-hexane or n-heptane, and the volume ratio of the nonpolar hydrocarbon solvent to the polar halocarbon solvent is 1:1-1.5.
[0010] Further, in step S1, the undesirable solvent is a methanol / n-hexane mixed solvent, and the volume ratio of methanol to n-hexane is 4-6:1.
[0011] Further, in step S1, the ratio of the total mass of vinyl tert-butyl ether and boron trifluoride diethyl ether to the volume of the mixed solution of the polar halocarbon solvent and the nonpolar hydrocarbon solvent is 1 g: 8-15 mL.
[0012] Further, in step S1, the prepolymer solid is added to an acidic solution at a solid-liquid ratio of 1 g: 10-15 mL, and the final concentration of hydrochloric acid in the acidic solution is 0.4-0.8 mol / L; the temperature of the heating, stirring and reflux reaction is 55-60℃, and the reaction time is 5-6 h.
[0013] Further, in step S2, the process of performing carboxymethylation modification includes the following steps: Step 1: Add the polyvinyl alcohol to an aqueous ethanol solution, add NaOH at 30-35℃ and stir to carry out an alkalization reaction for 1.5-2.5 hours to activate the hydroxyl groups of the polyvinyl alcohol side chain; Step 2: Then add chloroacetic acid aqueous solution to the reaction solution from Step 1, heat to 50-70℃, and stir at a constant temperature for 1-4 hours. Afterward, pour the reaction solution into a high-concentration ethanol aqueous solution to precipitate carboxymethyl polyvinyl alcohol. After filtration, washing and drying, pure carboxymethyl polyvinyl alcohol solid is obtained. The reaction formula is as follows: ; Where n is a positive integer.
[0014] Furthermore, in step 1, the mass concentration of the ethanol aqueous solution is 65-70%, preferably 70%.
[0015] Furthermore, in step 1, the molar amount of NaOH is 1.5-3 times the molar amount of polyvinyl alcohol, preferably 2 times. NaOH has two main functions: one is activation, causing the hydroxyl groups to react and generate sodium alkoxide; the second is neutralization of the subsequently added chloroacetic acid, inhibiting the hydrolysis side reaction of chloroacetic acid.
[0016] Furthermore, in step 2, the temperature of the stirring reaction is 60℃, and the reaction time is 2.5-3h.
[0017] Furthermore, in step 2, the mass concentration of the high-concentration ethanol aqueous solution is 75-80%, and the molar ratio of polyvinyl alcohol in step 1 to chloroacetic acid in step 2 is 1:0.9~1.2, preferably 1:1.1.
[0018] Furthermore, the additive is carboxymethyl polyvinyl alcohol with an average molecular weight of 8000~22000 g / mol and an syndiotacticity of 50-55%.
[0019] Preferably, the carboxymethyl polyvinyl alcohol has an average molecular weight of 15,000 to 17,000 g / mol and an syndiotacticity of 51 to 53%.
[0020] The present invention also discloses the application of the additive in the electrolytic preparation of high-purity iron powder. An acidic electrolyte containing iron ions and electrolyte is prepared, the additive is added to the electrolyte, a cathode plate and an anode plate are set up for electrodeposition, the cathode product attached to the cathode plate is scraped off and collected, and the cathode product is purified by hydrogen reduction heat treatment to obtain the high-purity iron powder.
[0021] Because the iron powder obtained by electrodeposition is highly active, its surface may be slightly oxidized. Therefore, after electrodeposition, the iron powder is subjected to hydrogen reduction heat treatment to remove impurities, remove iron oxides on the surface, and reduce the oxygen content. At the same time, after reduction in hydrogen, it is cooled in an inert atmosphere, so the surface of the iron powder can remain clean and active. The quality of the iron powder will not be significantly reduced due to hydrogen reduction.
[0022] Furthermore, in the acidic electrolyte, Fe 2+ The concentration is 20~60 g / L, the electrolyte concentration is 1-10 g / L, the electrolyte is sodium sulfate or potassium sulfate, the additive concentration is 0.1~0.5 g / L, and the pH is 3-4.
[0023] Furthermore, in the acidic electrolyte, Fe 2+ The concentration is 25~30 g / L, the electrolyte concentration is 5-6 g / L, the electrolyte is sodium sulfate or potassium sulfate, and the additive concentration is 0.25~0.3 g / L.
[0024] Furthermore, the anode plate is a titanium-based Y2O3-TiO2 composite coated electrode, and the loading of Y2O3-TiO2 on the titanium substrate is 10-25 g / m². 2 The molar ratio of Y to Ti is 0.004 to 0.006:1.
[0025] Furthermore, the cathode plate is made of 316L stainless steel, and undergoes surface degreasing and mechanical polishing pretreatment before use; the electrodeposition current density is controlled between 100 and 400 A / m. 2 Preferably 200 A / m 2 The electrolysis temperature is 10~50 ℃, preferably 20-25 ℃, and the electrolysis time is 1~10 h, preferably 5 h.
[0026] Furthermore, the process of removing impurities by hydrogen reduction heat treatment of the cathode product involves heat treatment in a hydrogen atmosphere at a temperature of 500 ℃ to 800 ℃, preferably 500-600 ℃, for a time of 30 to 40 min.
[0027] Furthermore, the titanium-based Y2O3-TiO2 composite coating electrode of the anode plate needs to be pretreated before use. The pretreatment process is as follows: place the titanium-based Y2O3-TiO2 composite coating electrode in acetone and ultrasonically wash for 5 min, ultrasonically wash in ethanol for 5 min, rinse with deionized water, and dry before use.
[0028] Furthermore, the cathode plate undergoes surface degreasing and mechanical polishing pretreatment before use. The pretreatment process is as follows: the 316L stainless steel plate is placed in an aqueous solution containing 20 g / L sodium phosphate and 5 g / L sodium hydroxide, and degreased at a temperature of 50~60 ℃ for 20~40 min, then rinsed with water; then coarsely ground with sandpaper until the surface is uniformly matte without mirror shine, ultrasonically cleaned with acetone for 5 min, ultrasonically cleaned with ethanol for 5 min, rinsed with deionized water, and dried before use.
[0029] Furthermore, the high-purity iron powder prepared is α-Fe phase with a purity of 4 N, free of iron oxide impurities, and a D50 particle size of 7~20 μm.
[0030] The additive of this invention has excellent applications in the electrodeposition preparation of iron powder. By lowering the critical current density for iron powder formation and inhibiting the hydrogen evolution reaction during the electrodeposition process, the additive improves the current efficiency of the electrodeposited iron powder and regulates the electrocrystallization process, thereby obtaining ultrafine iron powder. The ultrafine iron powder obtained by electrodeposition exhibits excellent properties.
[0031] In the preparation process of carboxymethyl polyvinyl alcohol (PVA) of this invention, PVA has poor water solubility and does not significantly improve current efficiency, making it difficult to use as an additive in the electrodeposition process for preparing iron powder. However, after carboxymethylation, PVA exhibits better water solubility. In acidic electrolytes, PVA possesses a strong hydrophilic carboxyl group, which can capture free water molecules, suppress hydrogen evolution side reactions, and improve current efficiency. Simultaneously, the hydroxyl groups readily adsorb onto the cathode substrate via lone pair electrons from oxygen atoms, significantly inhibiting the lateral diffusion and two-dimensional extension of iron atoms along the electrode surface. This results in the simultaneous generation of numerous isolated microcrystal nuclei, preventing the grains from overlapping and forming sheets. The extremely weak bonding force of these fine grains allows them to easily peel off from the cathode and enter the electrolyte, forming iron powder.
[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention successfully prepared carboxymethyl polyvinyl alcohol, an additive for electrodepositing iron powder, by cationic polymerization and carboxymethylation modification of vinyl tert-butyl ether. This additive can effectively reduce the critical current density for forming iron powder and significantly reduce the energy consumption for electrodepositing iron powder.
[0033] 2. The additive carboxymethyl polyvinyl alcohol prepared in this invention can form a large number of stable hydrogen bond networks in the electrolyte, reduce the amount of free water, and thus improve the current efficiency of electrodeposited iron powder to 91%.
[0034] 3. The additive carboxymethyl polyvinyl alcohol prepared in this invention can be adsorbed on the surface of the cathode plate, affecting the electrocrystallization process during electrodeposition, thereby obtaining ultrafine iron powder. Figure 2 The D50 particle size shown is 8.034 μm.
[0035] 4. The carboxymethyl polyvinyl alcohol prepared in this invention is used as an additive in the electrolytic preparation of iron powder. The iron powder obtained by electrodeposition is of the α-Fe phase, with a purity of 4N, and is free of iron oxide impurities. Figure 3 (As shown in Table 1). Attached Figure Description
[0036] Figure 1 The current density is that of the carboxymethyl polyvinyl alcohol electrodeposited iron powder prepared in Example 1 of the present invention.
[0037] Figure 2 This is a particle size distribution diagram of the product obtained in Example 1 of the present invention.
[0038] Figure 3 The comparison results are as follows: the XRD pattern of the product obtained in Example 1 of the present invention is compared with the XRD pattern of the iron powder standard card. Detailed Implementation
[0039] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0040] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0041] In this embodiment of the invention, the current efficiency is calculated using the following formula: ; in Let be the current efficiency, m be the actual mass of the current-deposited product, I be the electrolysis current, t be the electrolysis time, and k be the electrochemical equivalent. The electrochemical equivalent of electrodeposited iron is 1.042 g / (A·h).
[0042] Example 1: A method for preparing and applying an additive for low-energy electrolytic iron powder production. A method for preparing an additive for low-energy electrolytic iron powder production includes the following steps: S1: Using vinyl tert-butyl ether as a monomer and boron trifluoride diethyl ether as an initiator, the two were mixed at a molar ratio of vinyl tert-butyl ether to boron trifluoride diethyl ether of 100:1 to obtain raw material A. Raw material A was dispersed at a concentration of 1 g / 10 mL in a toluene-dichloromethane mixed solution with a volume ratio of 1:1.2. After reacting at -15 °C for 6 h, excess methanol / n-hexane precipitant (methanol to n-hexane volume ratio of 5:1) was slowly added dropwise. After precipitation, a white flocculent prepolymer solid was obtained. This solid was then added to a tetrahydrofuran / dilute hydrochloric acid mixed solution (tetrahydrofuran and 2 mol / L dilute hydrochloric acid were prepared at a solid-liquid ratio of 1 g:10 mL) at a solid-liquid ratio of 3:1. The mixture was stirred and refluxed at 60 °C for 5.5 h. After filtration, washing with methanol 2-3 times, and vacuum drying to constant weight, polyvinyl alcohol was obtained. The average molecular weight of polyvinyl alcohol was approximately 11400 g / mol.
[0043] S2: Add the polyvinyl alcohol obtained in step S1 into a 70% ethanol aqueous solvent. Add NaOH at a water bath temperature of 33°C. The molar amount of NaOH is twice the molar amount of polyvinyl alcohol. Stir and activate for 2 h. Then, under stirring conditions of 40°C and 200 r / min, slowly add an aqueous solution of chloroacetic acid. The dropping rate is controlled at 1~2 drops / second and the dropping time is about 15~20 min. The molar ratio of chloroacetic acid to polyvinyl alcohol is 1.1:1. After the dropping is completed, raise the water bath temperature to 60°C and stir the reaction at a constant temperature for 2.5 h. S3: After the reaction in step S2, the reaction solution was naturally cooled to room temperature. The solution was then poured into a 75% (w / w) ethanol aqueous solution for precipitation, resulting in the precipitation of carboxymethyl polyvinyl alcohol. The filter cake was washed three times with an 80% (w / w) ethanol aqueous solution, with each wash using approximately five times the mass of the filter cake. The mixture was then vacuum dried at 45 °C to obtain carboxymethyl polyvinyl alcohol. The average molecular weight of carboxymethyl polyvinyl alcohol is approximately 16000 g / mol, and its syndiotacticity is approximately 52%.
[0044] The carboxymethyl polyvinyl alcohol additive obtained in Example 1 was applied in the electrolytic preparation of high-purity iron powder, and the steps are as follows: Step 1: Prepare 2 L of Fe-containing solution 2+ An acidic electrolyte solution containing 30 g / L sodium sulfate, 5 g / L sodium sulfate, and 0.3 g / L carboxymethyl polyvinyl alcohol was prepared, with water as the solvent. The pH was adjusted to 3-4 using a 2 mol / L sulfuric acid solution.
[0045] Step 2: Anode plate titanium-based Y2O3-TiO2 composite coated electrode (5 cm × 10 cm), including a titanium substrate (5 cm × 10 cm) and a Y2O3-TiO2 composite coating loaded on the titanium substrate, the loading of the Y2O3-TiO2 composite coating is 15 g / m 2The molar ratio of Y to Ti is 0.005:1.
[0046] The titanium-based Y2O3-TiO2 composite coated electrode (5 cm × 10 cm) on the anode plate was ultrasonically washed in acetone for 5 min, ultrasonically washed in ethanol for 5 min, rinsed with deionized water, and dried before use.
[0047] The cathode plate is made of 316L stainless steel plate (5 cm × 10 cm). It is placed in an aqueous solution containing 20 g / L sodium phosphate and 5 g / L sodium hydroxide and degreased at 55 ℃ for 30 min. It is then rinsed with water, coarsely ground with sandpaper until the surface is uniformly matte without any mirror shine, ultrasonically cleaned with acetone for 5 min, ultrasonically cleaned with ethanol for 5 min, rinsed with deionized water, and dried before use.
[0048] Step 3: Add the acidic electrolyte prepared in Step 1 into the electrolysis device, and place the anode plate and cathode plate treated in Step 2 into the electrolysis device. The current density is 200 A / m. 2 Electrodeposition was carried out at a temperature of 25℃ for 5 hours. After the electrodeposition was completed, the cathode product attached to the cathode plate was scraped off and collected, yielding 4.7g of electrodeposited product. Step 4: The electrodeposition product collected in Step 3 was subjected to hydrogen reduction heat treatment to remove impurities. It was heat-treated at 600 °C for 30 min in a hydrogen atmosphere, and then cooled to room temperature in a nitrogen atmosphere to obtain 4.67 g of high-purity iron powder.
[0049] Example 1: The relationship between the current density and time during the electrodeposition process for preparing iron powder is shown in the figure. Figure 1 The particle size distribution diagram of the final high-purity iron powder obtained in Example 1 is shown below. Figure 2 The comparison results of the XRD pattern of the high-purity iron powder finally obtained in Example 1 with the XRD pattern of the iron powder standard card are shown in the figure. Figure 3 The results of determining the mass fraction of various elements in the high-purity iron powder obtained in Example 1 using ICP-OES are shown in Table 1.
[0050] Table 1 Chemical composition (wt%) of electrodeposited products .
[0051] According to the above experimental results, the current efficiency during electrodeposition can reach up to 91%, and the final iron powder has a D50 particle size of 8.034 μm, a purity of 4N, and a comprehensive energy consumption of 3.74 kWh / kg.
[0052] This invention successfully prepared carboxymethyl polyvinyl alcohol (CMA) as an additive for electrodepositing iron powder via cationic polymerization and carboxymethylation modification of vinyl tert-butyl ether. The CMA prepared by this invention exhibits excellent performance in electrodepositing iron powder, reducing the critical current density for iron powder formation, improving current efficiency, and producing ultrafine iron powder. Furthermore, this method is environmentally friendly and energy-saving, showing promising application prospects.
[0053] The electrodeposition experiment of Comparative Example 1 was the same as that of Example 1, except that no carboxymethyl polyvinyl alcohol additive was added to the acidic electrolyte. All other conditions remained the same. The electrodeposition reaction was carried out under the same current density and the same electrodeposition time. After the electrodeposition was completed, the cathode product attached to the cathode plate was scraped off and collected, and 4.27 g of electrodeposition product was obtained. The electrodeposition product was subjected to hydrogen reduction heat treatment to remove impurities. It was heat-treated at 600 °C for 30 min in a hydrogen atmosphere and then cooled to room temperature in a nitrogen atmosphere to obtain 4.25 g of high-purity iron sheet. The highest current efficiency of electrodeposition was 82%, and the electrodeposition product was iron sheet instead of iron powder.
[0054] Comparing the experimental results of Example 1 and Control Example 1, it can be seen that the additive carboxymethyl polyvinyl alcohol prepared by the present invention significantly improves the current efficiency and reduces the critical current density for forming iron powder, and iron powder can be obtained by electrodeposition under conventional current density.
[0055] Compare with Example 2, the experiment using vinyl tert-butyl ether as an additive in the electrolytic preparation of iron powder. The electrodeposition experiment of Comparative Example 2 was the same as that of Example 1, except that "in the electrolyte preparation step of step 1, the carboxymethyl polyvinyl alcohol in the electrolyte was replaced with vinyl tert-butyl ether of the same mass concentration", and the other conditions remained unchanged.
[0056] Compared with Example 2, at a current density of 200 A / m 2 Electrodeposition was performed at a temperature of 25℃ for 5 hours. After electrodeposition, the cathode product attached to the cathode plate was scraped off and collected, yielding 4.32 g of electrodeposited product. The electrodeposited product was then subjected to hydrogen reduction heat treatment to remove impurities. The product was heat-treated at 600℃ for 30 min in a hydrogen atmosphere and then cooled to room temperature in a nitrogen atmosphere to obtain 4.30 g of high-purity iron sheet.
[0057] In Comparative Example 2, the electrolyte additive carboxymethyl polyvinyl alcohol was replaced with vinyl tert-butyl ether, and an electrodeposition experiment was conducted. The highest current efficiency during the electrodeposition process was 83%, and the electrodeposition product obtained was an iron sheet. The overall energy consumption was 3.25 kWh / kg.
[0058] Example 2: Preparation method and application of an additive for low-energy electrolytic iron powder production. Example 2 The preparation method of the additive carboxymethyl polyvinyl alcohol is the same as that of Example 1, except that "in step S1, the molar ratio of vinyl tert-butyl ether to boron trifluoride ethyl ether is 100:1.5", and the other conditions remain unchanged, and carboxymethyl polyvinyl alcohol is finally obtained.
[0059] The average molecular weight of the polyvinyl alcohol solid obtained in step S1 of Example 2 was about 9400 g / mol, and the average molecular weight of the final carboxymethyl polyvinyl alcohol was about 14000 g / mol, with an syndiotacticity of about 51%.
[0060] The carboxymethyl polyvinyl alcohol prepared in Example 2 was used as an additive in the experiment of electrolytic preparation of high-purity iron powder. The experimental procedure was the same as in Example 1. In Example 2, the molar ratio of vinyl tert-butyl ether to boron trifluoride diethyl ether was changed during the preparation of carboxymethyl polyvinyl alcohol. The electrodeposition results were as follows: the current efficiency during electrodeposition was the highest at 85%, the D50 particle size of the obtained electrodeposited iron powder was 9.872 μm, the purity reached 4N, and the overall energy consumption was 4.12 kWh / kg.
[0061] Example 3: The experimental steps for preparing carboxymethyl polyvinyl alcohol and electrolytically preparing high-purity iron powder in Example 3 are the same as those in Example 1. The only difference is that the current density during electrodeposition in step 3 is changed, while the other conditions remain unchanged. The experimental results are shown in Table 2.
[0062] Table 2 Electrodeposited iron powder at different current densities .
[0063] As can be seen from Table 2, during the electrodeposition experiment, the current efficiency was around 90% as the current density increased. The D50 particle size of the obtained electrodeposited iron powder was around 8 μm, and the purity reached 4N.
[0064] Example 4: The experimental steps for preparing carboxymethyl polyvinyl alcohol and electrolytically preparing high-purity iron powder in Example 4 are the same as those in Example 1. The only difference is that the electrodeposition temperature in step 3 is changed, while the other conditions remain the same. The experimental results are shown in Table 3.
[0065] Table 3 Electrodeposited iron powder at different temperatures .
[0066] As shown in Table 3, during the electrodeposition experiment, the current efficiency gradually decreased with increasing electrodeposition temperature. This is because as the temperature rises, the iron in the electrolyte undergoes hydrolysis, reducing the Fe content in the electrolyte. 3+ Increased levels affect Fe 2+ The reduction was carried out. The resulting electrodeposited iron powder had a D50 particle size of approximately 8 μm and a purity of 4 N.
[0067] A comparison of the experimental results of Example 4 and Example 1 shows that the electrodeposition temperature has a significant impact on the current efficiency and performance of the final electrodeposited iron powder.
[0068] Example 5: The experimental steps for preparing carboxymethyl polyvinyl alcohol and electrolytically preparing high-purity iron powder in Example 5 are the same as those in Example 1. The only difference is that the electrodeposition time in step 3 is changed, while the other conditions remain the same. The experimental results are shown in Table 4.
[0069] Table 4 Electrodeposited iron powder at different times .
[0070] As shown in Table 4, during the electrodeposition experiment, the current efficiency remained relatively stable above 90% with increasing electrodeposition time. The D50 particle size of the obtained electrodeposited iron powder was approximately 8 μm, with a purity of 4 N. However, after 12.5 h, the current efficiency decreased due to the presence of Fe in the electrolyte. 2+ As the ion concentration decreased, the current efficiency dropped to 86%.
[0071] Five examples and three control experiments clearly demonstrate that the electrolyte additive prepared by cationic polymerization and carboxymethylation of vinyl tert-butyl ether can form a stable hydrogen bond network in the electrolyte, inhibit the occurrence of hydrogen evolution side reactions, improve the current efficiency of electrodeposited iron powder, reduce the critical current density for iron powder formation, and achieve low-energy preparation of high-purity iron powder.
[0072] In summary, the additive carboxymethyl polyvinyl alcohol prepared by this invention can be used for electrodeposition of ultrafine high-purity iron powder. The resulting electrodeposited product exhibits excellent performance, is an α-Fe phase, has a purity of 4 N, and a D50 particle size of 7-10 μm. This enables low-energy consumption, high-efficiency, high-purity, and continuous stable production of ultrafine high-purity iron powder.
[0073] The contents described in this specification are merely an enumeration of the implementation forms of the inventive concept, and the scope of protection of this invention should not be regarded as limited to the specific forms described in the embodiments.
Claims
1. The application of an additive in the electrolytic preparation of iron powder, characterized in that, An acidic electrolyte containing iron ions and electrolyte is prepared, the additive is added to the electrolyte, a cathode plate and an anode plate are set up for electrodeposition, the cathode product attached to the cathode plate is scraped off and collected, and the cathode product is purified by hydrogen reduction heat treatment to obtain the iron powder. The additive is prepared according to the following steps: S1: Using vinyl tert-butyl ether as monomer and boron trifluoride diethyl ether as initiator, the mixture is stirred for 4-8 hours at -20~-10℃ under inert gas protection in a mixed solution of polar halocarbon solvent and non-polar hydrocarbon solvent to generate a prepolymer. An excess of the undesirable solvent of the prepolymer is added dropwise to the reaction system. After precipitation to form a white flocculent prepolymer solid, the prepolymer solid is added to an acidic solution and heated and stirred under reflux. Then, it is filtered, washed and dried to obtain polyvinyl alcohol. S2: The polyvinyl alcohol is modified by carboxymethylation to obtain the additive.
2. The application according to claim 1, characterized in that, The molar ratio of vinyl tert-butyl ether to boron trifluoride ethyl ether is 100: 0.8~1.2, and the ratio of the total mass of vinyl tert-butyl ether and boron trifluoride ethyl ether to the volume of the mixed solution of polar halocarbon solvent and nonpolar hydrocarbon solvent is 1g: 8-15mL; the inert gas in step S1 is nitrogen or argon.
3. The application according to claim 1, characterized in that, In the mixed solution of polar halocarbon solvent and nonpolar hydrocarbon solvent described in step S1, the polar halocarbon solvent is dichloromethane or chloroform, and the nonpolar hydrocarbon solvent is toluene, n-hexane or n-heptane, and the volume ratio of the nonpolar hydrocarbon solvent to the polar halocarbon solvent is 1:1-1.
5. In step S1, the undesirable solvent is a methanol / n-hexane mixed solvent; In step S1, the prepolymer solid is added to an acidic solution at a solid-liquid ratio of 1 g: 10-15 mL. The acidic solution is a mixture of hydrochloric acid and tetrahydrofuran, wherein the final concentration of hydrochloric acid is 0.4-0.8 mol / L. The temperature of the heating, stirring and reflux reaction is 55-60℃, and the reaction time is 5-6 h.
4. The application according to claim 1, characterized in that, Step S2, the carboxymethylation modification process, includes the following steps: Step 1: Add the polyvinyl alcohol to an aqueous ethanol solution, add NaOH at 30-35℃ and stir to carry out an alkalization reaction for 1.5-2.5 hours to activate the hydroxyl groups of the polyvinyl alcohol side chain; Step 2: Then add chloroacetic acid aqueous solution to the reaction solution in Step 1, heat to 50-70℃, stir and react at a constant temperature for 1-4 hours, then pour the reaction solution into a high concentration ethanol aqueous solution for precipitation, carboxymethyl polyvinyl alcohol is precipitated, filtered, washed and dried to obtain pure carboxymethyl polyvinyl alcohol solid.
5. The application according to claim 4, characterized in that, In step 1, the mass concentration of the ethanol aqueous solution is 65-70%, and the molar amount of NaOH is 1.5-3 times the molar amount of polyvinyl alcohol; in step 2, the mass concentration of the high-concentration ethanol aqueous solution is 75-80%, and the molar ratio of polyvinyl alcohol in step 1 to chloroacetic acid in step 2 is 1:0.9~1.
2.
6. The application according to claim 1, characterized in that, The additive is carboxymethyl polyvinyl alcohol, with an average molecular weight of 8000~22000 g / mol and an syndiotacticity of 50-55%.
7. The application according to claim 1, characterized in that, In the acidic electrolyte, Fe 2+ The concentration is 20~60 g / L, the electrolyte concentration is 1-10 g / L, the electrolyte is sodium sulfate or potassium sulfate, the additive concentration is 0.1~0.5 g / L, and the pH is 3-4.
8. The application according to claim 7, characterized in that, The anode plate is a titanium-based Y2O3-TiO2 composite coated electrode, and the cathode plate is a 316L stainless steel plate. The cathode plate undergoes surface degreasing and mechanical polishing pretreatment before use. The electrodeposition current density is controlled between 100 and 400 A / m. 2 The electrolysis temperature is 10~50 ℃ and the electrolysis time is 1~10 h; the process of removing impurities by hydrogen reduction heat treatment of cathode products is to carry out heat treatment in a hydrogen atmosphere, the heat treatment temperature is 500 ℃~800 ℃ and the heat treatment time is 30~40 min.
9. The application according to claim 7, characterized in that, The prepared iron powder is α-Fe phase with a purity of 4 N, free of iron oxide impurities, and has a D50 particle size of 7~20 μm.
Citation Information
Patent Citations
Anionic polyvinyl alcohol textile size and preparation method thereof
CN119569920A